Stakeholders’ Perception of Coconut Palm Insurance Scheme: A Study on the Coastal States of India - Rajasenan, D.; Rajeev, B. (International Coconut Community, 2013)
The Coconut Palm Insurance Scheme (CPIS) is a mechanism, devised to endow effective risk management aid, to those coconut growers who are likely to be impacted by non-preventable natural factors as well as pests and diseases. This study analyses the perception of the stakeholders for drawing empirical validity, so as to appraise sustainability of CPIS as a measure towards financial inclusion. 528 samples, encompassing Kerala, Karnataka, Tamil Nadu, Goa and Maharashtra states, classified into three regions, were taken using multi-stage proportionate random sampling technique with a view to develop a recurrent scheme to assist the coconut growers. Analyses and inferences, based on Factor Analysis, point out that growers across the regions are convinced that the scheme is necessary for a crop like coconut and, accordingly, the scheme seems to have achieved its goal.